The Influence of Customer, Supplier, and Competitor Knowledge Sourcing on the Eco-Innovation Performance of Small and Medium Enterprises - Nur Izzati, Abd Rahman (2024)
The increasing demand for food due to the rapid growth in the global population has led to rising greenhouse gas emissions associated with increased production. This has raised awareness of environmental issues. The concept of eco-innovation, which aims to mitigate environmental harm, has gained global prominence. Although there is an increasing awareness of climate change and its impacts, the exploration of ecoinnovation in the food manufacturing sector remains limited, both on a global scale and specifically in Malaysia. Despite Malaysia's active promotion of eco-innovation among industrial players, particularly small and medium-sized enterprises (SMEs), there are still some challenges that need to be addressed. Implementing eco-innovation can pose challenges for many SMEs. Therefore, using the resource-based view theory, this study investigates the influence of customer, supplier, and competitor knowledge sourcing on eco-innovation performance within food manufacturing SMEs in Malaysia. The population frame was obtained from the business directory of the Federation of Malaysian Manufacturers for 2020. Questionnaires were distributed to SME owners or managers. Out of the 196 questionnaires distributed, 50 were returned, with a response rate of 25.5%. Through a multiple regression analysis, the results found a significant positive relationship between customer, supplier, and competitor knowledge sourcing with eco-innovation performance. The findings also highlight that food manufacturing SMEs in Malaysia utilised competitor knowledge sourcing the most, followed by customer and supplier knowledge sourcing. The results have practical implications for SMEs, policymakers, and other industry players. These support them to make informed decisions by identifying strategic resources for SMEs to enhance their eco-innovation performance. Furthermore, this study extends the resource-based perspective theory in the context of eco-innovation. Finally, the study provides insights into the importance of knowledge-sourcing practices for eco-innovation performance in SMEs.